Cultural and climatic history of Coba, a lowland Maya city in Quintana Roo, Mexico - Leyden, B. W.; Brenner, M.; Dahlin, B. H. (Quaternary Research, 1998)
Lake Coba, within the archaeological site of Coba, provides evidence bearing on lowland Maya development, Palynological and geochemical data record multidecadal precipitation cycles from a 8.80-m, >8370-yr lake-sediment sequence terminating on bedrock. Late Classic sedimentation rates are rapid, but an anthropogenically derived colluvium layer is lacking, Initial vegetation was medium semi-deciduous and swamp forest. Forest clearance began 1650 B.C. (Early Preclassic) and maize first occurred at 850 B.C. (Middle Preclassic). Lakeside milpas existed until A.D. 720 (Late Classic) and then were moved from the city center as urbanization intensified and Lake Coba was diked as a reservoir. Coba was at most briefly vacated during the Classic Collapse and was abandoned after A.D. 1240, although some habitation persisted. The paleoecological record matches the archaeological history for Coba, but pervasive disturbance muted the climatic signal, as the Late Classic drought is barely evident. The question whether economic trees were maintained within the city is unresolved, Maize cultivation allowed the Maya to develop a complex society and support a large population, but dependence on maize was ultimately doomed by variable rainfall. Precipitation in extreme years was insufficient to support crops, while native vegetation was not directly affected by drought that devastated Maya agriculture, (C) 1998 University of Washington.
Yz880Times Cited:59Cited References Count:46